The Unistellar Exoplanet Campaign: Citizen Science Results and Inherent Education Opportunities. (1st January 2023) - O'Conner Peluso, Daniel; Esposito, Thomas M.; Marchis, Franck; Dalba, Paul A.; Sgro, Lauren; Megowan-Romanowicz, Colleen; Pennypacker, Carl; Carter, Bradley; Wright, Duncan; Avsar, Arin M.; Perrocheau, Amaury; ,
Abstract: This paper presents early results from and prospects for exoplanet science using a citizen science private/public partnership observer network managed by the SETI Institute in collaboration with Unistellar. The network launched in 2020 January and includes 163 citizen scientist observers across 21 countries. These observers can access a citizen science mentoring service developed by the SETI Institute and are also equipped with Unistellar Enhanced Vision Telescopes. Unistellar technology and the campaign's associated photometric reduction pipeline enable each telescope to readily obtain and communicate light curves to observers with signal-to-noise ratio suitable for publication in research journals. Citizen astronomers of the Unistellar Exoplanet (UE) Campaign routinely measure transit depths of ≳1% and contribute their results to the exoplanet research community. The match of the detection system, targets, and scientific and educational goals is robust. Results to date include 281 transit detections out of 651 processed observations. In addition to this campaign's capability to contribute to the professional field of exoplanet research, UE endeavors to drive improved science, technology, engineering, and mathematics education outcomes by engaging students and teachers as participants in science investigations, that is, learning science by doing science.